Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1359/jbmr.1998.13.6.1011
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Trabecular and Cortical Bone Turnover and Bone Mass and Strength to Bisphosphonate YH529 in Ovariohysterectomized Beagles with Calcium Restriction

Abstract: Thirty-six beagles, 18 months of age, underwent ovariohysterectomy (OHX) or a sham operation. Sham-operated animals were given a diet with standard calcium (1.4%) (group 1, n ‫؍‬ 6) or a restricted calcium diet (0.14%) (group 2, n ‫؍‬ 6). The OHX animals were given the restricted calcium diet and YH529 orally with respective daily doses of 0, 0.02, 0.1, and 0.5 mg/kg of body weight (groups 3-6, n ‫؍‬ 6 each) for 12 months. At the end of this period, the lumbar bone mineral densities (BMDs) in groups 2 and 3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…(25) Skeletal metabolic heterogeneities are of interest in the study of the pathophysiology of metabolic bone disorders including osteoporosis and also may help us to understand the different treatment responses observed with regard to bone mass and fracture risk at different skeletal sites. (6,9,11,14) Whyte et al found that it was not possible to predict regional heterogeneity in postmenopausal osteoporotic skeletal dynamics without histomorphometric analysis but predicted that radionuclide methods might allow these measurements in the future. (26) Unlike histomorphometry, which essentially is limited to the iliac crest, 18 F-fluoride PET has the potential to measure kinetics at any skeletal site although to date there is only limited experience in the spine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(25) Skeletal metabolic heterogeneities are of interest in the study of the pathophysiology of metabolic bone disorders including osteoporosis and also may help us to understand the different treatment responses observed with regard to bone mass and fracture risk at different skeletal sites. (6,9,11,14) Whyte et al found that it was not possible to predict regional heterogeneity in postmenopausal osteoporotic skeletal dynamics without histomorphometric analysis but predicted that radionuclide methods might allow these measurements in the future. (26) Unlike histomorphometry, which essentially is limited to the iliac crest, 18 F-fluoride PET has the potential to measure kinetics at any skeletal site although to date there is only limited experience in the spine.…”
Section: Discussionmentioning
confidence: 99%
“…(10) Studies on regional turnover or regional blood flow are possible in animal models but in man histomorphometry is used to infer information on regional metabolism. (11)(12)(13) However, this is a relatively invasive technique that generally is limited to the iliac crest and is not always practical in a clinical setting.…”
mentioning
confidence: 99%
“…Pre-clinical studies in larger animals (dogs and mini pigs) consistently show absence of a BP effect on periosteal bone formation [18,19,[36][37][38][39]. More detailed studies have been conducted in rats and mice, although in these species conflicting results exist.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…(14) Ultimate load (UL) to failure at the time of bone fracture, stiffness, maximum deformation, and energy were determined from the test charts. The value of the bending moment to failure (BMF, N⅐mm) was then calculated from the following equation: BMF ϭ 1/4 ϫ UL (N) ϫ L (40 mm).…”
Section: Mechanical Testing Of the Lumbar Body And Midfemurmentioning
confidence: 99%